Perbedaan Hasil Belajar melalui Penerapan Model Pembelajaran Berbasis Masalah Berbantuan Komik Fisika dengan Pembelajaran Konvensional pada Siswa Kelas Viii SMPN 1 Labuapi Tahun Ajaran 2013/2014 - Tri Kurniawan; Joni Rokhmat; Jannatin Ardhuha (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This is quasy experiments research aimed to find out the differences of physics study result through problem based learning model with comic physics assist and conventional learning on students of grade VIII SMPN 1 Labuapi in academic year 2013/2014. This research used design of Posttest Only Control Group Design, while the sampling technique used is cluster and purposive sampling. Population of this research is students SMPN 1 Labuapi of grade VIII while the sampling are the students of grade VIII B as experiment group and the students of grade VIII C as control group. The data of this study is analyzed by using two tail t-test of polled varians, those are 6,25 forÃÂ  thint and 2,0294 for ttable with degree of freedom 36 and significantce 5%. This result ( thint > ttable ) H0 will be rejected and Ha will be accepted which indicates that the physics study result through problem based learning model with comic assist is different from that through conventional learning onÃÂ  students of grade VIII SMPN 1 Labuapi in academic year 2013/2014.